Control of the gut microbiome by fecal microRNA - Shirong Liu; Howard L. Weiner (Microbial Cell)
Since their discovery in the early 90s, microRNAs (miRNAs), small non-coding RNAs, have mainly been associated with posttranscriptional regulation of gene expression on a cell-autonomous level. Recent evidence has extended this role by adding inter-species communication to the manifold functional range. In our latest study [Liu S, et al., 2016, Cell Host & Microbe], we identified miRNAs in gut lumen and feces of both mice and humans. We found that intestinal epithelial cells (IEC) and Hopx+ cells were the two main sources of fecal miRNA. Deficiency of IEC-miRNA resulted in gut dysbiosis and WT fecal miRNA transplantation restored the gut microbiota. We investigated potential mechanisms for this effect and found that miRNAs were able to regulate the gut microbiome. By culturing bacteria with miRNAs, we found that host miRNAs were able to enter bacteria, specifically regulate bacterial gene transcripts and affect bacterial growth. Oral administration of synthetic miRNA mimics affected specific bacteria in the gut. Our findings describe a previously unknown pathway by which the gut microbiome is regulated by the host and raises the possibility that miRNAs may be used therapeutically to manipulate the microbiome for the treatment of disease.